Analisis Pengujian Panas Kabel Nyaf Pada Sistem Kelistrikan Dinamo Kendaraan e-Niaga Geni Biru Roda 3 - Purnomo, Ari (Journal of New Energies and Manufacturing, 2023)
Cables are an important part in the manufacture of electric motorcycles. The cable serves to conduct electric current from the battery to all parts that require electric power. Because the cable uses copper which is a heat conductor and uses a flammable plastic/rubber wrapper, this risk must be minimized or eliminated. This research was conducted to identify and analyze the cable heat in the lighting system. The research method that will be used is to use tools such as clamp meters and thermo scanners. The clamp meter will detect the current flowing then the thermo scanner will detect the temperature on the NYAF cable. From these two tools, the cable heat test data obtained in the form of the maximum allowable temperature and how many amperes are allowed. The test results with a current variation of 1-28 amperes produce a temperature of 38.5°C to 43.5°C with a convection electric heat rate of -22.06 W with a heat flow rate from low temperature to high temperature.